Fungi in Rice Straw, Cane Straw, Maize Straw and Their Potential as Decomposer - Ika Rochdjatun Sastrahidayat; Chintya Ivana Situmorang; Anton Muhibuddin (KH. A. Wahab Hasbullah University, 2018)
Organic material decomposition is the reorganizing process of the organic material by microbes in the controlled circumstances. The microbes which were used in general such as fungi, bacteria or yeast. Aerobic yeasts is one of the microbes needs oxygen to work. Yeast was obtained by the exploration of the rice straw, maize straw and cane straw in Dau, Malang, East of Java. By the result of the microscopic exploration and observation through the microscope, it was obtained 9 yeast isolates and 3 fungi isolates. 2 yeast isolates and 1 fungi isolate from the rice straw, 2 yeast isolates and 1 fungi isolate from the maize straw, and 5 yeast isolates and 1 fungi isolate from the cane straw. The identification results were obtained Candida parapsilosis, Bellera oryzae, Kluyveromyces thermotolerant, Candida tropicalis, Debaryomyces hansenii, Wickerhamomyces anomalus, Pichia membranfaciens, Cryptococcus wieringae. The highest potential yeast as an organic fertilizer decomposer is Cryptococcus wieringae and the lowest is Bullera oryzae. Keywords : Candida, Pichia, Cryptococcus, Bullera, Kluyveromyces, DebaryomycesWickerhamomyces, Fusarium and Trichoderma